Effect and Underlying Mechanism of Ultrasonic Pretreatment on the Quality of Fresh Fish Vermicelli - WANG Xiaoyun, GAO Xia, YOU Juan, YIN Tao, LIU Ru (Shipin Kexue)
In this study, fresh fish vermicelli was made from surimi and starch using a cutting process. The effects of ultrasonic pretreatment at different powers (120, 150, 180, 240 and 300 W) for different periods (5, 10, 15, 20 and 25 min) on the cooking quality, sensory quality and texture characteristics of fresh fish vermicelli were explored. The underlying mechanism was clarified by measuring the particle size and viscosity of the paste as well as the infrared spectrum, moisture distribution and microstructure of the vermicelli. The results showed that with the increase in ultrasonic power and time, the particle size and viscosity of the paste initially decreased and then increased, while the opposite trend was observed for the percentage of bound water (A21). Decreased ultrasonic time and power improved the dispersion and uniformity of raw materials, increased the water-binding capacity, and promoted fish vermicelli to form a uniform and dense microstructure. Increased ultrasonic time and power caused protein degradation, reduced the microstructural uniformity of fresh fish vermicelli, and deteriorated its quality. Ultrasonic treatment at 120 W for 10 min increased the tensile strength and stretching distance of fresh fish vermicelli increased by 23.98% and 21.08%, respectively, and decreased the broken rate and grout vomiting value decreased by 28.27% and 11.54%, respectively, compared with the control group without ultrasonic treatment. Under this ultrasonic condition, fish vermicelli had the highest sensory score.